Continued exposure to D‐galactose in postnatal period may inhibit excessive primordial follicle reduction in rats exposed prenatally to D‐galactose. Issue 17 (2nd September 2022) - Dovom, Marzieh Rostami; Noroozzadeh, Mahsa; Mosaffa, Nariman; Zadeh‐Vakili, Azita; Piryaei, Abbas; Rahmati, Maryam; Azar, Mahbanoo Farhadi; Tehrani, Fahimeh Ramezani
Abstract: We aimed to compare the ovarian reserve of rats exposed to oral D‐galactose during prenatal and early life with rats exposed to D‐galactose only during the prenatal period. Fifteen female pregnant Wistar rats were randomly divided into three groups. The first and second groups were fed a D‐galactose enriched diet (35%) from the third day of pregnancy to parturition (PP) and the third day to the end of lactation (PL), respectively. The control group (C group) was fed a standard diet. The study population was the female offspring of three groups (PP′, PL′, and C′), in which some reproductive factors were examined between 45 and 50 days of age. When compared with the PP′ group, the number of primordial follicles was significantly higher in the PL′ group at PND 45–50 (40 vs. 30; p  = .01); however, the antimullerian hormone level was significantly reduced in the PL′ group versus control group (−2.2, 95% confidence interval [CI]: −2.83, −1.53 ng/ml p  = .000), and follicle‐stimulating hormone level significantly increased in PP′ group versus control (4.5 mIU/ml, 95% CI: 1.40–7.62, p  = .005). There was no significant difference in leukocyte infiltration or antiovarian antibody among the groups. Continued exposure to D‐galactose during the lactation period inhibits the primordial follicle loss in rats in terms of producing fewer atretic follicles.